Psychotic symptoms during stimulant treatment for attention-deficit/hyperactivity disorder - Sá, Teresa (2020)
Introduction: Attention-deficit/hyperactivity disorder (ADHD) is a common neurodevelopmental disorder. Pharmacological treatment, either alone or in combination with psychosocial interventions, is important in the therapeutic strategy. Psychostimulants remain the most effective medication and are generally well tolerated. However, one of its rare but significant side effects is development of psychotic symptoms. Objectives: To perform a literature review about the risk of psychotic symptoms during ADHD treatment with stimulants and discuss possible pharmacological treatment implications.Methods: A literature search was conducted on PubMed database using the terms “ADHD”, “central nervous system stimulants”, and “psychosis”. The search was supplemented with data retrieved from published guidelines.Results and discussion: ADHD diagnosis has been increasing, as well the use of stimulants for its treatment. However, using these drugs is not without controversy. ADHD pharmacological treatment is rarely associated with psychotic symptoms. Reported symptoms include hallucinations and paranoid delusions, and occasionally also euphoria, grandiosity, and other mania and hypomania features. These symptoms are generally short-lived and self-limited within days after stimulant discontinuation. One study comparing amphetamines and methylphenidate suggested that the former was more likely to cause psychosis compared with the latter. Additionally, study authors agreed that stimulant-induced psychosis seems to be associated to susceptibility factors.Conclusion: Psychostimulants are highly beneficial for ADHD patients. However, small studies and case reports suggest an association with new-onset psychotic symptoms. Physicians should be aware that psychotic symptoms may arise during stimulant ADHD treatment. Further investigation is required to identify patients who are most at risk of experiencing such adverse events.